THE NET PRESENT VALUE OF INVESTMENTS IN RAISING AND EXPLOITING WALNUT PLANTATIONS - Zorica Sredojevic; Damir Nađ; Vasili Vasilije Ostojić (Ekonomika Poljoprivrede (1979))
The subject of the research is the application of the net present value and methods based on it for the assessment of the economic justification of raising walnut plantations of Sejnovo variety on 3 and 10 ha, with same cultivation form and planting system. The research was conducted on the basis of data collected during the period 2022-2024. in Western Serbia. For a plantation of 3 ha, indicators of economic effectiveness per unit area are lower than indicators for a plantation of 10 ha, i.e. 53,378 €/ha<8,375 €/ha (net present value) and 69,204 €/ha<73,089 €/ ha (capitalised value). Pay-back period for a 10 ha is shorter than a 3 ha i.e. 9.24 years<9.64 years and internal rate of return for a 10 ha is higea than a 3 ha by 0.57%, i.e. 37.92%>37.35%. It is concluded that investing in establishing and exploiting walnut plantations on an area of 10 ha is more economically